Corrosion Resistance Enhancement of Reinforced Concrete in Marine Environment by Partial Replacement of Black Rice Husk Ash - Walairat Chandra-ambhorn; Eakarach Bumrungthaichaichan; Chayanit Rotchan; Narunat Haema; Patthranit Wongpromrat; Santi Wattananusorn (Key engineering materials, 2023)
In this work, the black rice husk ash (BRHA), a pozzolanic material, was used as a partial replacement in concrete with the weight percentages of 0%, 10%, 20%, 30%, 40% and 50% for enhancing the corrosion resistivity in the marine environment. The compressive strength, corrosion by accelerated corrosion test by impressed voltage (ACTIV), and chloride (Cl − ) penetration of concrete specimens were investigated after 28 days of curing. For corrosion and chloride penetration analyses, the 20% of BRHA replacement specimen was the most effective concrete specimen because the deformation was not observed within 19 days of the test. The cement specimens with lower BRHA percentages were cracked due to the development of stress by the rust formation. For higher BRHA percentages, the protective Fe 2 O 3 was dissolved due to the acidic environment caused by higher chloride accumulation in the cement specimens. The steel rebar was then aggressively attacked by the chloride and it was finally broken. Therefore, the optimization of the BRHA percentage is needed to minimize corrosion. However, the longer curing time of 20% BRHA replacement specimen is required for increasing the compressive strength because its compressive strength is slightly lower than the standard.
Keywords: Concrete Corrosion and Durability; Concrete and Cement Materials Research; Corrosion Behavior and Inhibition